In Vitro Effects of Oligosaccharides on Bacterial Concentration and Fermentation Profiles in Dairy Calf Colon Content - Hendraningsih, L.; Sumantri, C.; Ahmadi, J.; Muktiani, A.; Sulistyanto, B. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Some oligosaccharides have been shown to modify colonic micro flora composition andactivity in many humans and some animal species. Some oligosaccharides tend to elevate beneficialbacteria and the others depress harmful bacteria in gastrointestinal tract. Â However, little data areavailable on their fermentation characteristics by the ilea microbial community, and their effects onthe colon micro flora composition. The aim of this study was to evaluate the in vitro effect ofoligosaccharides from apple and banana peel extraction and mannan-oligosaccharide (MOS)commercial on concentrations of the total anaerobic bacteria, Bifidobacterium, Lactobacilli, Coliformad Esheihia oli populatio i dai alfâ€™ olo otets. To goups of 2 ales fed a ilkreplacer (1 week old) and fibrous pellets (3 weeks-old) were sacrificed 5 h after the morning meal. Ineach group, colon content were pooled and diluted with, diluted by Lowe medium. Extraction ofapple, banana peel, and MOS were tested in vitro versus a control. Each bottle was incubated induplicate for each treatment and at 370C in a shaking water bath. Bacterial concentrations weredetermined at 48 H and inoculated in selected media for each bacteria group and supernatant weretaken for fatty acids (VFA) measurement. Result showed in general, oligosaccharides were notresulted VFA concentration than control bottle in both groups even tend to inclined, specificallybanana peel. Apple peel and banana peel slightly increase total anaerob and lactobacilli in bothgroup but could not depress the E. coli. On the other hand MOS seems the most effective indepressing coli. Based on our results, oligosaccharides were fermented by bacteria of ilea contentsin dairy calves and its fermentation led to a selective stimulation of host bacteria.Key Words: Oligosaccharides, Dairy Calf, Colon, Selective Media